The Morphometry of Body and Organ Indices of Broiler Chickens [Gallus gallus gallus (Linnaeus, 1758)] After Administration of Blue-spotted Maskray Liver Extract [Neotrygon caerulopunctata (Last, White & seret, 2016)] - Saragih, Hendry Tri Sakti Surya Gunawan; Ria Vinola Septhya Sari; Shintia Oktaviana; Filda Mega Ayunda (Universitas Sulawesi Barat, 2024)
The broiler chicken industry is a primary provider of protein for the Indonesian population. For optimal growth, broiler chickens require feed with a high protein content, which currently remains expensive due to the majority of its raw materials being imported products. Waste from fish processing, such as the liver of the blue-spotted stingray (Neotrygon caerulepunctata), is rich in protein and can serve as an economical alternative feed for broiler chickens. This study aims to evaluate the impact of blue-spotted stingray liver extract on the morphometric structure and organ indices of broilers. A total of 300 male and female Cobb 500 DOC broiler chickens were raised until 16 days old using a Completely Randomized Design (CRD) with 4 treatments, each with 5 replications consisting of 15 chickens. The treatments of blue-spotted stingray liver extract (EHP) were administered per kg of basal feed (PB) with variations of Control (0% EHP/kg PB), T1 (0.5% EHP/kg PB), T2 (1% EHP/kg PB), and T3 (2% EHP/kg PB). Parameters observed included morphometry and organ indices such as intestinal weight, intestinal length, muscle length, muscle area, bursa weight, and spleen weight. The results showed that the T3 treatment group with 2.0% stingray liver extract demonstrated significant improvements in morphometry and organ indices such as intestinal weight, intestinal length, muscle length, muscle area, bursa weight, and spleen weight compared to the Control group (0% EHP). The T3 group also exhibited better growth performance compared to the Control group.